2009
DOI: 10.2214/ajr.07.3330
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of Acute Right Lower Quadrant Pain: Importance of Increased Intraabdominal Fat Echo

Abstract: An increased intraabdominal fat echo on sonography is highly specific for the presence of RLQ inflammatory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 20 publications
5
27
0
3
Order By: Relevance
“…Another important limitation of sonography compared with CT has been its inability to stage the severity of inflammation. 16 This study showed that with the combination of ES and sonography, patients with acute appendicitis could be categorized into those with mild, moderate, and severe disease, and the findings correlated well with the surgical findings. A recent study by Lee et al 16 also tried to visualize the inflammatory changes in periappendiceal fat in acute appendicitis on sonography by detecting the changes in the echogenicity; however, we think that these can be better assessed on ES, as shown in this study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Another important limitation of sonography compared with CT has been its inability to stage the severity of inflammation. 16 This study showed that with the combination of ES and sonography, patients with acute appendicitis could be categorized into those with mild, moderate, and severe disease, and the findings correlated well with the surgical findings. A recent study by Lee et al 16 also tried to visualize the inflammatory changes in periappendiceal fat in acute appendicitis on sonography by detecting the changes in the echogenicity; however, we think that these can be better assessed on ES, as shown in this study.…”
Section: Discussionmentioning
confidence: 63%
“…16 This study showed that with the combination of ES and sonography, patients with acute appendicitis could be categorized into those with mild, moderate, and severe disease, and the findings correlated well with the surgical findings. A recent study by Lee et al 16 also tried to visualize the inflammatory changes in periappendiceal fat in acute appendicitis on sonography by detecting the changes in the echogenicity; however, we think that these can be better assessed on ES, as shown in this study. Moreover, with increasing literature on the medical management of acute appendicitis, 17 it would be worthwhile to use ES to triage such patients to decide on their surgical or medical approach.…”
Section: Discussionmentioning
confidence: 63%
“…There is examination of the diagnostic qualities of some secondary signs: inflammatory fat changes (SN 91%, SP 76%), caecal wall thickening (SN 25%, SP 88%), lymph nodes (SN 32%, SP 62%) and peritoneal fluid (SN 51%, SP 71%). Lee et al 34 2009 Prospective study of 317 adult patients. Found that an increased intra-abdominal fat echo was seen in patients with appendicitis (SN 73%, SP 98%).…”
Section: Authormentioning
confidence: 99%
“…6). 34 The mesentery can provide both a path for disease spread and barrier for infection as it potentially walls off inflamed areas such as an acute appendix. A useful method for determining if there is an increase in mesenteric echogenicity is to compare the contralateral side of the patient as a baseline.…”
Section: Secondary Sonographic Signsmentioning
confidence: 99%
See 1 more Smart Citation